Gingipains disrupt bone homeostasis via dual regulation of osteogenesis and osteoclastogenesis through exosomal miR-146a-5p/TRAF6 signaling - Dong, Jiachen; Liao, Yue; Sun, Mengjun; Chen, Huiwen; Zhou, Kecong; Zhang, Huanyu; Zhou, Wei; Song, Zhongchen (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundGingipains are virulence factors released by Porphyromonas gingivalis that contribute to periodontal destruction by disrupting bone metabolism. This study aimed to evaluate the dual effects of gingipains on bone metabolism by examining their impact on osteogenesis and osteoclastogenesis, hypothesizing that gingipains regulate these processes via direct and exosomal pathways involving microRNA signaling.MethodsClinical samples of gingival crevicular fluid, subgingival plaque, and gingival tissues were collected from 15 patients with stage III-IV periodontitis and 15 healthy controls. The effects of gingipains on bone marrow mesenchymal stem cells (BMSCs) and RAW264.7 macrophages were assessed using cell proliferation assays, qPCR, western blot, microarray analysis, and dual-luciferase reporter assays. A rat periodontitis model was used to validate the findings in vivo.ResultsPeriodontitis patients exhibited elevated levels of lysine- and arginine-specific gingipains, C5a, and RANKL (p < 0.05). Gingipains inhibited BMSCs proliferation and osteogenic differentiation in a dose-dependent manner while promoting osteoclastogenesis in RAW264.7 macrophages through BMSCs-derived exosomes. Gingipains reduced the levels of miR-146a-5p in exosomes, which enhanced osteoclast differentiation through the miR-146a-5p/TRAF6 signaling pathway. Animal models confirmed that gingipains aggravated alveolar bone loss, which was mitigated by miR-146a-5p overexpression.ConclusionGingipains disrupt bone metabolism by inhibiting BMSCs osteogenesis and promoting osteoclastogenesis through communication via exosomes. Targeting miR-146a-5p offers a potential therapeutic approach to counter gingipain-induced periodontal destruction.